Application of The UTAUT Model In Determining Behavioral Intentions To Use Shopee Paylater - Linofal Fakhrin; Yulia A. Widyaningsih (Journal Research of Social Science, Economics, and Management, 2025)
In the era of digitalization, it is increasingly facilitated by the existence of several e-commerce services that provide electronic money services as a tool for conducting transactions, in addition to cellular payments there are also those that result in paylater, both of which aim to make it easier for the public to use the new features provided by each e-commerce platform trade. Shopeepay Later is present as a form of non-cash electronic money transactions that can help the public make transactions easier. This study aims to find out what factors make someone have the intention of using Shopeepay Later. This study uses a survey method conducted by distributing questionnaires through Google Forms to collect data. The method used is purposive sampling with certain criteria. The number of samples in this study were 214 respondents with the criteria of respondents being shopee application users aged 18 years and over and not using shopeepay later. The study used the UTAUT model with multiple linear regression analysis. The results of this study indicate that performance expectancy and the social influence on the intention to use shopeepay later. Meanwhile, effort expectancy and facilitating condition have no effect on behavioral intentions to use shopeepay later.